2018
DOI: 10.24135/pjr.v24i1.400
|View full text |Cite
|
Sign up to set email alerts
|

Social media and disaster communication: A case study of Cyclone Winston

Abstract: Abstract:This article presents an analysis of how social media was used during Tropical Cyclone Winston, the strongest recorded tropical storm that left a wake of destruction and devastation in Fiji during February 2016. Social media is increasingly being used in crises and disasters as an alternative form of communication. Social media use in crisis communication varies according to the context, the disaster and the maturity of social media use. Fiji's experience during TC Winston contributes to the growing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…The greater the ability to anticipate a disaster, the greater the possibility for reducing or mitigating its effects and for developing potential solutions. The Finau et al (2018) study demonstrated how important social media was in communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater the ability to anticipate a disaster, the greater the possibility for reducing or mitigating its effects and for developing potential solutions. The Finau et al (2018) study demonstrated how important social media was in communication.…”
Section: Discussionmentioning
confidence: 99%
“…People have been telling stories of close escapes. (Singh, interview, 2018) According to Finau et al (2018) in a post-Winston study, while social media did not replace traditional communication or media, it demonstrated 'innovative and serendipitous uses' ranging from informing citizens, sharing experiences and as a 'rallying point': 'Social media has created a space for Pacific Islanders' voices to be heard and the severity of Cyclone Winston being a consequence of anthropogenic climate change'.…”
Section: Social Adaptation Of Tropical Cyclone Winston In Fijimentioning
confidence: 99%
“…Those impacted in vulnerable areas or in regions potentially at risk are the target population. They are affected by disaster characteristics such as location, demographic details, information accessibility and information flow between them and other parties [ 45 ].…”
Section: Structure Of a Resilient Communication Ecosystemmentioning
confidence: 99%
“… Characteristics Descriptions based on information ecology perspective Adaptation (coevolution) Social media enhances coevolution within the disaster communication setup by exchanging real time information about the event [ 51 ]. Heterogeneity (diversity) Cases exhibit diversity among information and communication tools, i.e., Twitter, Facebook, organizational websites, and mass media [ 52 ], and list various actors such as remote actors [ 37 , 38 ], responsible agents [ 40 , 41 ], transmitters [ 43 ], and targets [ 45 ]. Driving force (keystone species) Cases show highly skilled, voluntary entities or governmental organizations could be a driving force for adaptation.…”
Section: Structure Of a Resilient Communication Ecosystemmentioning
confidence: 99%
“…In the Pacific, a digital revolution has resulted in drastic changes in the means by which Pacific islanders commu-nicate, access information, and engage in public/political discourse (Cave, 2012). Research has demonstrated that in the Pacific, social media has become a means of communication, disaster awareness, political debate and activism, and even identity formation and rejuvenation (Brimacombe, Kant, Finau, Tarai, & Titifanue, 2018;Finau et al, 2018;Titifanue, Tarai, Kant, & Finau, 2016;Webb-Gannon & Webb, 2019). This commentary argues that as the Pacific Region undergoes its digital revolution, issues such as the Free West Papua Movement act as a catalyst for regional concern and action at the community level.…”
mentioning
confidence: 99%